The responsible corporation in a global economy - Crouch, Colin, 1944-; Maclean, Camilla (Oxford : Oxford University Press, 2012)
Bringing together academics and practitioners, this volume examines the increasingly important arena of global economic governance and the role played by major corporations from a diverse range of perspectives.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 17, 2012).
Includes bibliographical references and index.
Keywords: Social responsibility of business